Managing Universities : Policy and Organizational Change from a Western European Comparative Perspective - Bleiklie, Ivar, 1948-; Enders, Jürgen; Lepori, Benedetto, 1965- (Palgrave Studies in Global Higher Education, 2017)
This book asks how modern universities are organized and managed, and questions whether 30 years of university reforms have resulted in stronger managerial structures and leadership control. It further asks whether current organisational and decision-making structures can be explained by public reform policies. The book offers a coherent, empirically grounded and theoretically driven presentation of data and core ideas behind a large scale comparative study of 26 universities across eight European countries. It focuses on the strength of university managerial structures, the role of academics, and how universities relate to and depend on their environment: to governments and other actors; to funders; to evaluators; and to external stakeholders. It further explores how higher education policies are shaped by and affect universities. Written by a cross-disciplinary team of European scholars, this book is unique both in its wide coverage and the depth of its analyses. It will be of great interest to scholars, graduate students and advanced undergraduates in the fields of organisation theory and sociology, policy studies, comparative public policy and administration, and higher education studies. It will also be of interest to higher education policy makers and administrators.